Regulation by FurC in Anabaena Links the Oxidative Stress Response to Photosynthetic Metabolism. (21st May 2019) - Sevilla, Emma; Sarasa-Buisan, Cristina; Gonzlez, Andrs; Cases, Rafael; Kufryk, Galyna; Peleato, M Luisa; Fillat, Mara F
Abstract: The FUR (Ferric Uptake Regulator) family in Anabaena sp. PCC 7120 consists of three paralogs named FurA (Fur), FurB (Zur) and FurC (PerR). furC seems to be an essential gene in the filamentous nitrogen-fixing strain Anabaena sp. PCC 7120, suggesting that it plays a fundamental role in this organism. In order to better understand the functions of FurC in Anabaena, the phenotype of a derivative strain that overexpresses this regulator (EB2770FurC) has been characterized. The furC -overexpressing variant presented alterations in growth rate, morphology and ultrastructure, as well as higher sensitivity to peroxide than Anabaena sp. PCC 7120. Interestingly, the overexpression of furC led to reduced photosynthetic O2 evolution, increased respiratory activity, and had a significant influence in the composition and efficiency of both photosystems. Comparative transcriptional analyses, together with electrophoretic mobility shift assays allowed the identification of different genes directly controlled by FurC, and involved in processes not previously related to PerR proteins, such as the cell division gene ftsZ and the major thylakoid membrane protease ftsH . The rise in the transcription of ftsH in EB2770FurC cells correlated with reduced levels of the D1 protein, which is involved in the PSII repair cycle. Deregulation of the oxidative stress response in EB2770FurC cells led to the identification of novel FurC targets involved in the response to H2 O2 through different mechanisms. These results, together with the effect of furC overexpression on the composition, stability and efficiency of the photosynthetic machinery of Anabaena, disclose novel links between PerR proteins, cell division and photosynthesis in filamentous cyanobacteria.